DOI: 10.1007/978-3-540-79590-2_17
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Performance of Tactile/Proximity Sensors Made of Carbon Microcoils

Abstract: By mimicking Meissner's corpuscles, carbon microcoils (CMCs) were embedded into an elastic resin to produce biomimetic proximity/tactile sensors. The CMC sensors were found to have a high elasticity, high sensitivity, high discrimination ability, and a high performance, as well as being easily made in a micron size. These sensors have potential applications in robotic surgery, medical treatment, and diagnosis, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Chen et al [60] extended this research by investigating the effects of composite thickness on impedance. This was done by using 10 × 10 mm 2 composites of 7 wt% CMC uniformly dispersed in soft polysilicone with thicknesses of 3, 5, and 7 mm.…”
Section: Tactile Sensormentioning
confidence: 98%
See 1 more Smart Citation
“…Chen et al [60] extended this research by investigating the effects of composite thickness on impedance. This was done by using 10 × 10 mm 2 composites of 7 wt% CMC uniformly dispersed in soft polysilicone with thicknesses of 3, 5, and 7 mm.…”
Section: Tactile Sensormentioning
confidence: 98%
“…This was done by using 10 × 10 mm 2 composites of 7 wt% CMC uniformly dispersed in soft polysilicone with thicknesses of 3, 5, and 7 mm. Impedance increased with applied load; and thickness influenced sensitivity and the maximum range of applied load [60]. Katsuno et al [53] reported the impedance and phase angle changes of 5 wt% double helical CMC/silicone rubber composite (6 × 6 × 2 mm 3 ) under different loads.…”
Section: Tactile Sensormentioning
confidence: 99%
“…HCFs have shown excellent electron field emission characteristics [ 27 , 28 , 29 , 30 ] and wide band absorption of electromagnetic waves [ 31 , 32 , 33 , 34 , 35 ]. Because of their unique morphology and properties, HCFs have been proposed for potential applications in polymer additives [ 36 , 37 , 38 ], supercapacitor electrodes [ 39 , 40 ], catalysts [ 41 ], catalyst supports [ 42 , 43 ], hydrogen adsorption [ 39 , 44 , 45 ], generator or detector of magnetic field [ 46 ], an electrical inductors [ 21 ], micro/nanospring [ 47 ], sensors [ 21 , 48 , 49 ], nanodevices [ 50 ], etc .…”
Section: Introductionmentioning
confidence: 99%
“…weight and size) for integration into a wider range of robotic systems including light-weight flying robots and compact manipulators for operation in confined spaces. To date, prominent examples of such sensing systems include capacitive tactile proximity sensors based on silver nanowires and polymer film [35] and carbon microcoils [36]. Since, the former uses the same capacitive range for both proximity and tactile sensing, the sensor is not able to distinguish between static proximity and tactile inputs.…”
Section: Sensory-physical Design Of the Module: Seamless Measurement mentioning
confidence: 99%